Influence of Dispositional Mindfulness on Emotional Intelligence as Ability - Pimentel Bernal, Paul Marcelo (Pontificia Universidad Católica del Perú, 2020)
The purpose of this quantitative, correlational, descriptive, and cross-sectional research that uses structural equations is to contribute to and make progress in the understanding of mindfulness and emotional intelligence as ability, to explain the influence of mindfulness on emotional intelligence, to explain the direction between the constructs, to assess the positive relationship between emotional intelligence and its equivalence with trait emotional intelligence. Based on the ability model of emotional intelligence (Caruso, Mayer & Salovey, 2002), the trait model of emotional intelligence (Schutte et al., 1998, 2009), the comprehensive dimensional model of emotional intelligence (Shutte & Malouff, 2013), the dispositional mindfulness model (Shapiro, Carlson & Astin, 2006), and the measurement models of emotional intelligence as one-dimensional character trait (Schutte et al., 1998). The target population from which the sample will be drawn will be selected from private postgraduate schools in Peru, using statistical inferences and structural equation analysis. The results will fill gaps in the literature for empirically evaluating the influence effect of mindfulness on ability emotional intelligence, the link between emotional intelligence and other variables will be achieved in the face of the need to increase research and provide better estimates of its dimensions and its relationships (Quaglia et al., 2016). In light of the results, it is suggested that dispositional mindfulness has a positive and significant relationship with emotional intelligence as a skill and as a trait, and it is corroborated that it can be a platform for its development in organizations. Key Words: Emotional Intelligence, Mindfulness
Keywords: Inteligencia emocional; https://purl.org/pe-repo/ocde/ford#5.02.04